The effect of using educational complexes on the achievement and retention of rhetoric among fifth grade literary students (Journal of the College of Basic Education, 2022)
The current research aims to identify the impact of the use of educational complexes in the collection and retention of rhetoric among students of the fifth literary grade.The research sample consisted of (152) male and female students who were divided into two groups: an experimental group consisting of (76) male and female students (40) male and (36) female students, and a control group consisting of (63) male and female students (40) male and (36) female students. . Before the start of the actual teaching, the students of the two groups were rewarded in a number of statistical variables, namely: the previous information test, the scores of the Arabic language subject in the final test of the previous academic year, the chronological age calculated in months, the academic achievement of the fathers, the academic achievement of the mothers.The subjects that will be studied in the experiment were identified, and the behavioral objectives were formulated in the light of the general objectives and content of the subjects. After that, the researcher prepared model plans in teaching the subjects of the experiment, so they followed the educational complexes for the students of the experimental group, and in the traditional way for the students of the control group.An achievement test was prepared in rhetoric, and the researcher confirmed its sincerity, stability, and objectivity, and applied it to the students of the two research groups at the end of the experiment, which lasted a full semester.After analyzing the data using the t-test for two independent samples, the researcher concluded that there were statistically significant differences between the achievement of the students of the two research groups at the level of 0.05 in favor of the students of the experimental group, as well as retention of achievement.In the light of the results of the research, the researcher concluded that the educational complexes have an effectiveness and a positive impact in increasing the achievement of the fifth grade literary students in the rhetoric subject.In the light of the results of the research, the researcher recommended designing modern curricula in a way that helps and facilitates the application of the technology of educational complexes in the preparatory stage, and the provision of the necessary equipment and devices and the preparation of books, resources and modern teaching aids in preparatory schools to facilitate the use of the technology of educational complexes.And as a complement to this research, the researcher suggested conducting studies aimed at identifying the impact of the use of educational complexes on the fifth literary grade students' acquisition of grammatical concepts and the attitude towards matter.